A disaster communication plan for Higher Education Institutions in the Island Province of Occidental Mindoro, Philippines - Nielo, Leomar Christian G. (Frontiers in Communication, 2024)
Natural disasters, as they impede development and exacerbate poverty, have been the foremost concern of developing countries like the Philippines. With this, the Philippine Disaster Risk Reduction Management Act (RA 10121) highlights the role of Higher Education Institutions (HEIs) in disaster resiliency and requires the incorporation of disaster communication in their institutions. Since disaster communication is considered to be one of the most valuable assets during disasters, academic institutions are provided visibility, credibility, and concrete direction to address chaos, and confusion and to secure the safety of their stakeholders. The study created SANDATA, a disaster communication plan for HEIs in Occidental Mindoro to provide disaster communication strategies that can be used by them in securing a disaster-resilient academic environment. The output of this study was materialized using factor and thematic analysis and through the 300 respondents assigned for the quantitative data and 30 respondents for the qualitative data. These determined the disaster communication strategies employed by HEIs under the disaster stages of the Crisis Emergency Risk Communication (CERC) Theory, stakeholders’ identified communication challenges as experienced by them, and their recommendations to improve the existing strategies of their institutions.